The Participation of the Families: Interference in the Management and Support to the Learning - Cristina Beatriz Carriego (Universidad Autónoma de Madrid, 2016)
The presented work constitutes and advance in the ongoing research entitled "Pedagogic Work and social and normative context" that is currently perfomed in grammar schools at the city of Buenos Aires. This articles analyzes which characteristics assume the participation of families in function to their socioeconomical status and the type of school management. The research took place departing from the quality ethnographic study that proposes the systematic comparison of the four grammar schools of the city of Buenos Aires. The selection of the cases combines the variables: socioeconomical status (upper and lower) and the type of school management (public, and private). First, the results show the structures provided at the schools for the participation of families. Secondly, it is analyzed the form win which parents express their disconformities and the degree of inherence that their claims have on the school management. Finally it is offered a short description of the commitment assumed by the parents and the learning process of their children. We can conclude that the participation of the families at the school takes form in function to the different conditioning, economical as well as cultural. Let us consider that it is necessary to take into consideration the different shades that are acquired by  the participation of the families in function with the context so the mentioned process could operate as a reassurance of improvement and no as a advocate of greater inequity.